A bold pumpkin plan [book with audioplayer] - Hudson, Katy ([Library Ideas, LLC], 2024)
Timid Hedgehog wants to build a special house this year, but first she must get the pumpkin she selected home--a task that requires her to overcome her fears and ask for help from some other animals.